IMPLEMENTATION OF THE SMART TOURISM STRATEGY FOR TOURISM DEVELOPMENT AT SINGKIL BEACH KARANG PAKIS NUSAWUNGU, CILACAP, CENTRAL JAVA - Damiasih, Damiasih; Wati, Okta Adi Laksmana (Universitas Padjadjaran, 2024)
Tourism development and management do not exclude the possibility of embracing the Fourth Industrial Revolution, including the use of information and communication technology to realize smart tourism. This is crucial because tourism development must adapt to technological advancements and innovations to provide the best service to tourists. This research employs a mixed-method approach that integrates quantitative and qualitative methods. Quantitative data is derived from statistical indicators of visits to understand the diversity of viewpoints and questionnaire responses from tourists. Qualitative data includes interviews with informants, observations, and research documentation processed through SWOT analysis to formulate strategies based on identified internal and external factors. The study found that the management of the Singkil Beach Karang Pakis tourist destination had not fully maximized its tourism potential. Therefore, a tourism destination development strategy is formulated based on the concepts of strengths-opportunities, weaknesses-opportunities, strengths-threats, and weaknesses-threats. The concept of smart tourism is applied through the implementation of smart experiences, destinations, and business ecosystems as part of the development strategy. By integrating information and communication technology, this concept promises innovation in tourist destination management. An increase in tourist visits, thereby enhancing the economic quality for stakeholders, such as Pokdarwis, tourism managers, and the local community marked the successful implementation of the smart tourism concept.